IbM Kader Pengurusan Jenazah Muslimah Desa Wedomartani (Kecamatan Ngemplak Kabupaten Sleman D.I.Yogyakarta) - Akhmad Fauzy; Syaefudin Ali Akhmad (UII, 2018)
The lack of availability of Muslimah dead body (Modin)’s administrators in the Wedomartani village, so far in taking care of the women’s dead body always need help from men. Whereas in the Wedomartani village the number of women is higher than men so this causes a serious problem. Based on this problem, through IbM Cadre Management of Muslimah Dead Body in Wedomartani Village is done in the process of practical education and cadre at the management of the muslimah dead body. The implementation of the program is using the method of training and practice directly using the body of the doll as a miniature of the original body. The results of training and practice directly make the women who become cadre stewardship became capable of having good knowledge about how to take care of the dead body in accordance with Islamic Shari'a.